2004
DOI: 10.1002/jms.607
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the hydrolysis products of AlCl3·6H2O by electrospray ionization mass spectrometry

Abstract: The hydrolysis reactions of AlCl3 in 0.1 M aqueous solutions at pH 3.27-4.20 were monitored by electrospray ionization time-of-flight mass spectrometry (ESI-ToF MS) as a function of time. The cationic and anionic ESI mass spectra of aluminum(III) solutions gave strong evidence of the presence of a variety of monomeric and polymeric complexes. Competition between the OH- and Cl- ligands within the same aluminum core was observed. The influence of the sample cone voltage on the product distribution was also expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(110 citation statements)
references
References 22 publications
12
98
0
Order By: Relevance
“…This is consistent with the results of Rämö et al (21). As shown in Figure 3b According to a previous study (22), the presence of TMA adducts also was observed in the samples due to pH adjustment by TMA. In this study, another very intense signal at m/z 113 was observed as well; this may be assigned to [K2Cl] + .…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with the results of Rämö et al (21). As shown in Figure 3b According to a previous study (22), the presence of TMA adducts also was observed in the samples due to pH adjustment by TMA. In this study, another very intense signal at m/z 113 was observed as well; this may be assigned to [K2Cl] + .…”
Section: Resultssupporting
confidence: 93%
“…Therefore, too low or high sample cone voltage was not suitable for detecting all aluminum species. This is consistent with the previous literature that low or high sample cone voltage could not benefit aluminum species analysis at a high aluminum concentration [14]. Other studies also indicated that sample cone voltage responsible for ion extraction from the ionization source into the mass analyzer affected ESI-MS analysis result [27][28][29].…”
Section: Effect Of Sample Cone Voltage On the Esi-ms Analysissupporting
confidence: 91%
“…In a previous MS study, 1 we showed that the mix of species in aqueous aluminum chloride solutions is more complex than suggested by models obtained by potentiometric methods. 2 -6 Cationic and anionic electrospray ionisation (ESI) mass spectra of aluminum(III) solutions provided strong evidence for the presence of a variety of monomeric and polymeric complexes, from Al 1 to Al 32 core complexes, with different amounts of water molecules.…”
Section: Introductionmentioning
confidence: 88%